2019
DOI: 10.15678/eber.2019.070401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Efficacy and Entrepreneurial Self-Efficacy on the Entrepreneurial Intentions of Graduate Students: A Study among Omani Graduates

Abstract: The objective of this research is to study the entrepreneurial intention of Omani graduate students by introducing self-efficacy as a mediating variable in Social Cognitive Career Theory (SCCT). Research Design & Methods: Two hundred and sixty-three Omani graduate students were surveyed using a self-administered questionnaire. An entrepreneurial intention model was developed and tested using AMOS. Findings: The results revealed that the effect of self-efficacy on the entrepreneurial intention of graduate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
1
16
0
5
Order By: Relevance
“…These results suggest that entrepreneurial intention of college students was more likely to be strengthened through entrepreneurial self-efficacy. The finding corroborates those of preceding studies which drew similar conclusions ( Rauch and Hulsink, 2015 ; Udayanan, 2019 ; Anwar et al, 2020 ; Islam et al, 2020 ). However, some previous researchers found that entrepreneurial self-efficacy is a partial mediator between entrepreneurship education and entrepreneurial intentions ( Rauch and Hulsink, 2015 ; Anwar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that entrepreneurial intention of college students was more likely to be strengthened through entrepreneurial self-efficacy. The finding corroborates those of preceding studies which drew similar conclusions ( Rauch and Hulsink, 2015 ; Udayanan, 2019 ; Anwar et al, 2020 ; Islam et al, 2020 ). However, some previous researchers found that entrepreneurial self-efficacy is a partial mediator between entrepreneurship education and entrepreneurial intentions ( Rauch and Hulsink, 2015 ; Anwar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“… Thompson (2009) defines an individual’s entrepreneurial intention as “a person intends to establish a new enterprise and consciously plans to do so at some time in the future.” As a state of consciousness before action ( Buttar, 2015 ), entrepreneurial intention plays a key role in the decision of individuals to establish a new business ( Bird, 1988 ; Nabi et al, 2010 ), and is considered to be the best predictor of entrepreneurial behavior ( Krueger et al, 2000 ; Carsrud and Braennback, 2011 ). Recently, many researchers have begun to focus on the entrepreneurial intentions of college students ( Sanchez, 2013 ; Støren, 2014 ; Zhang et al, 2014 ; Udayanan, 2019 ). Many factors are considered to be determinants of entrepreneurial intentions, such as personality factors, environmental factors, and population factors ( Indarti and Rostiani, 2008 ).…”
Section: Theories and Assumptionsmentioning
confidence: 99%
“…In addition, he indicated that entrepreneurial and managerial skills are significant determiners of perceived self-efficacy in entrepreneurship. Udayanan (2019) highlights that higher education can play a vital role in building entrepreneurial self-efficacy. Alsaidan and Zhang (2018) have likewise noted that increasing students’ “vocational knowledge” would positively affect their entrepreneurial self-efficacy and intentions.…”
Section: Resultsmentioning
confidence: 99%
“…Their results show considerable business experience among academics, which translates into consulting activities, although not the creation of technological spinoffs. Udayanan (2019) studies entrepreneurial intention among 263 university graduates, taking self-efficacy for a mediator variable, evaluated with the AMOS software. We find that the ESE mediates the effect of self-efficacy on GEI.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%